AB0058 Cytokine secretion and cytotoxic activity of natural killer cells in behÇet's disease. (23rd January 2014) - Cosan, F.; Aktas-Cetin, E.; Akdeniz, N.; Emrence, Z.; Gecgel, F.; Erbag, G.; Dogru, A.; Deniz, G.; Cefle, A.
Abstract : Background: Behcet's disease (BD) is a multi-system inflammatory disorder with recurrent inflammation attacks. BD pathogenesis includes genetical, environmental and immunological factors. The main genetic susceptibility is HLA-B*51, but the mechanism is unknown. HLA molecules play a key role with the interaction with natural killer (NK) cells which are one of the components of the innate immune system. They have the ability to both lyse target cells and serve as regulators of immune responses by releasing Th1, Th2 and Th17 type cytokines. Objectives: In this study, cytokine secretion and cytotoxic activity of NK cells in BD were investigated. Methods: The study group consists of BD patients (n=26, mean age=37.2±9.7) with mucocutaneous involvement and healthy subjects (n=12, mean age=32.5±8). The patients had not received any immunsupresive treatment. Peripheral blood mononuclear cells (PBMC) were used as effector cells and K562 cell line was used as target cell. PBMCs stained with CD107a were incubated with K562 cells with an effector:target (10:1) for four hours. Cells were stained with anti-CD16 antibody for the determination of CD107a expression by flow cytometry. Cytotoxic activity (by using CFSE-labeled K562 as target cells), expression of NK cell receptors and surface markers, intracellular IL-5, IL-10, IL-17 and IFN-glevels in CD16 + NK cells were also determined by flow cytometry. Statistical analyses were performed by Mann Whitney U test. Results: Although the percentages of NK, CD16 bright CD56 dim, CD16 dim CD56 bright subsets, NKp46 and NKG2D expressions were found similar in both groups, there was a significant difference in NK cell subsets. IFN-gsecreting NK1 cell subsets were found to be higher in BD group (p=0.001). However, IL-5 + CD16 + NK2 cells, IL-17 + CD16 + NK17 and IL-10 secreting NK regulatory cell ratio were found significantly decreased in BD group (p=0.001). Although the CD107a expression levels were found decreased in BD group, cytotoxic activity did not show any difference between groups with CFSE method (p=0.03). Conclusions: We found a polarization to NK1 cell subset in BD. Although no difference was found in the cytotoxic activity, the degranulation ratio of NK cells is significant lower in BD. Our findings revealed that increased NK1 cell subsets might play role in BD pathogenesis. Disclosure of Interest: None Declared